Peer relationships: differences considering intellectual abilities and age - Jelić, Marija M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Problems with peers are more common among children with intellectual disabilities (ID) than typical development (TD) children. As a lack of research in this field states the heterogeneity of the samples in relation to the level of disability and age, which is important for the ability to plan preventive programs and targeted interventions. The aim of this study was to examine the association between intellectual status and age with peer relationships. The study included 206 students aged 12 to 18 years, of which 76 with mild ID and 130 TD. Peer relationships were measured by Rahim Organizational Conflict Inventory (compromise, problem solving, yielding, avoidance and domination) and by subscale Problems with peers from The Strenghts and Difficulties Questionnaires. The main findings showed that students with mild ID have more problems with peers than TD students. Unlike TD students, at secondary school age students with mild ID more often yielding and avoidance conflicts. At later age dominance is less frequent in both groups of students, and problem solving and compromise are statistically more frequent in students with mild ID group than in TD peers group. At the end of the article, it was pointed out that cognitive deficits are not a key factor for more problems with peers students with mild ID than TD students and that further research has to examine the impact of environmental factors on various aspects of peer relationships.